ACCOUNTING IN MEXICO. - Benedetto, A. F. (The Accounting Review, 1934)
The article presents views of the author on novel business and accounting practices in Mexico. These novelties were very amusing and interesting to us and compared strangely with the way of doing things in the U.S. We in the U.S., are complaining about the various records, forms, which have to be kept for purposes of the Revenue, Securities and Securities and Exchange Acts. This complaint would become a mild one, indeed, if our corporations should be compelled to conform to the regulations now existing in Mexico. In the auditing of the cash account we encountered a strange procedure that is followed by the banks in that country. The banks do not return the canceled checks with the bank statement. The reason behind such practice is that the canceled check is the only evidence the bank has for the charge it has made to the company's account and therefore it keeps the check for its own protection. At first such a practice appeared amusing, but on second thought one can not deny that banks were following a safer policy in this respect than our own do. In the U.S. it would be an easy matter for a customer on receiving his canceled checks from the bank to abstract one and then claim that the bank had erred in charging his account for the amount of the check he had abstracted.